An Overplayed Hand: France and the Bretton Woods International Monetary System - Eugene N. White; Michael D. Bordo; Dominique Simard (Rutgers University, Department of Economics, 1994)
We reinterpret the commonly held view in the U.S. that France, by following a policy from 1965 to 1968 of deliberately converting their dollar holdings into gold helped perpetuate the collapse of the Bretton Woods International Monetary System. We argue that French international monetary policy under Charles de Gaulle was consistent with strategies developed in the interwar period and the French Plan of 1943. France used proposals to return to an orthodox gold standard as well as conversions of its dollar reserves into gold as tactical threats to induce the United States to initiate the reform of the international monetary system towards a more symmetrical and co-operative gold-exchange standard regime.
Keywords: E5; 330; Bretton Woods; France; international monetary system